(untitled) (Scientific journal of the Fergana State University, 2024)
During the years of independence in Uzbekistan, the opportunity arose to study the historical, cultural, socio-philosophical and spiritual-ethical heritage of our people, unjustly forgotten or rejected during the Soviet period. It became an objective necessity to restore the names of thinkers whose research was prohibited or studied monastically, and to analyze their heritage from a national-democratic point of view. Approach these studies from the point of view of a new methodology; show their significance in the education of the mature generation and in development. The purpose of the study is to study the history of social and philosophical thought in our country and highlight it in the years of independence. The time has come to collect, summarize and objectively evaluate the available empirical material. Such research will help to correctly determine the directions of our future scientific and theoretical work and focus our attention on important and topical issues. Spirituality is one of the most pressing issues today. Over the years of independence, a new social philosophy has been formed. The article analyzes scientific research conducted in the first years of independence. Brief summaries of books and works of philosophers and scientists are highlighted. Research methods: Such methods of scientific knowledge as analysis and synthesis, retrospective analysis, content analysis, dialectical approach, historicity, continuity, comparative analysis and observation were used. The results of the study include the following: - Critical analysis of research conducted during the Soviet period; - Justification that new social and philosophical thinking is an objective and moral necessity in the years of independence; - show that national ideology and new social and philosophical thinking are dialectically harmonious realities; In conclusion, we can say that after the independent development of the Republic of Uzbekistan, its strategic goals are the construction of a democratic rule of law state and a free civil society, the formation of a mature generation with high morals. One of the effective ways to achieve this strategic goal is to study the values of our people, our nation, socio-historical, political and spiritual experience, compatible with national development, and apply them in spiritual life.